(untitled) (Comprehensive Journal of Science, 2026)
The choice of studying the city-state (Athens) is due to the political practice that this state was distinguished by. It was a unique democratic model and made it the first nucleus in discussing political issues. This is of course with some reservations about this democratic practice. However, the political experience of Athens is successful because the Greek thinkers adopted the method of observation and planning in order to ensure political stability for the Greek tribes and overcome the social conflicts that existed and that stood in the way of the progress of society